A clinical study of morphological patterns of cutaneous adverse drug reaction and its causality assessment in tertiary care hospital of central India - Shende, Tanaji R.; Siddiqui, Riyaz A. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Adverse reactions to drugs are as old as drug. Cutaneous adverse drug reactions are the most common type of drug reaction. Most cutaneous adverse drug reactions are important as they are frequently the reason for discontinuation of drug therapy. Looking to this matter the study was undertaken. Method: It was an observational study conducted at NKP Salve Institute of Medical Science & Research Centre, Nagpur Maharashtra. A total number of 80 patients having cutaneous adverse drug reaction were evaluated. All the patients were assessed for cutaneous adverse drug reaction during the study period and the information was carefully recorded in standard Adverse drug reaction (ADR) form and Naranjo’s algorithm was used for causality assessment of adverse drug reaction. Result: The maximum study subjects were in the age group of 41-50 years (32-50%) followed by the age group of 31-40 years (25%) followed by other age groups. In study group male to female ratio was 11.5:8.5. Majority of cutaneous adverse drug reactions comprise of fixed drug eruption which is 45%. Most of the cutaneous ADR’s were caused by antibiotics (42.5%) followed by Non-steroidal anti-inflammatory drugs (NSAIDS) (20%). The study subjects were in probable causality assessment of Naranjo’s scale i.e. 82.5% followed by definite in (12.5%) and possible (5%). Conclusion: The fixed drug eruption was the most common cutaneous adverse drug reaction and most of these drugs eruptions were caused by antimicrobial agents. The study provided the base line information about the prevalence of cutaneous adverse drug reaction and their morphological distribution amongst different age group, gender and the causative drug.